Electromagnetic pulse response of planar screens. (21st February 2018) - Araneo, Rodolfo; Lovat, Giampiero; Burghignoli, Paolo; Celozzi, Salvatore
Abstract: A general numerical method for calculating the time‐domain characteristics of the electromagnetic field generated by a pulsed dipole in the presence of a planar multilayered screen is presented. The method involves the efficient evaluation of classical Sommerfeld integrals and an inverse Fourier transform to recover the time‐domain field from the frequency‐domain field. For sufficiently thin screens with highly conductive properties, an analytical method, based on a modified Cagniard–de Hoop approach, is also presented to validate the results.